2008
DOI: 10.1002/jts.20355
|View full text |Cite
|
Sign up to set email alerts
|

Financial and social circumstances and the incidence and course of PTSD in Mississippi during the first two years after Hurricane Katrina

Abstract: Hurricane Katrina was the most devastating natural disaster to hit the United States in the past 75 years. The authors conducted interviews of 810 persons who were representative of adult residents living in the 23 southernmost counties of Mississippi before Hurricane Katrina. The prevalence of posttraumatic stress disorder (PTSD) since Hurricane Katrina was 22.5%. The determinants of PTSD were female gender, experience of hurricane-related financial loss, postdisaster stressors, low social support, and postdi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
286
3
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 288 publications
(320 citation statements)
references
References 33 publications
28
286
3
3
Order By: Relevance
“…These women were also more likely to have experienced military sexual trauma, to be unemployed, and to be disabled [41]. Importantly, Galea et al have shown that there may be reciprocal associations between financial loss and PTSD [43]. Specifically, they showed that, in the aftermath of Hurricane Katrina, financial loss predicted PTSD diagnostic status 2 years posttrauma.…”
Section: Financial Problems and Homelessnessmentioning
confidence: 99%
See 1 more Smart Citation
“…These women were also more likely to have experienced military sexual trauma, to be unemployed, and to be disabled [41]. Importantly, Galea et al have shown that there may be reciprocal associations between financial loss and PTSD [43]. Specifically, they showed that, in the aftermath of Hurricane Katrina, financial loss predicted PTSD diagnostic status 2 years posttrauma.…”
Section: Financial Problems and Homelessnessmentioning
confidence: 99%
“…Recent research focusing specifically on Veterans has shown that important risk factors for homelessness include extreme poverty, a postmilitary psychiatric disorder, and social isolation. Additional studies with homeless Veterans have found associations between PTSD and homelessness and financial loss [41,43]. Homeless female Veterans were more likely to screen positive for PTSD than nonhomeless female Veterans.…”
Section: Financial Problems and Homelessnessmentioning
confidence: 99%
“…Because of that most of the definitions of a disaster follows a sociological point of view in their description (Lopez-Ibor, 2006). Furthermore, it has been recognized that mental health outcomes are not only dependent on the individual traumatic experiences and the losses, but also from the destruction of the social context which happens after a disaster (Kawachi & Subramanian, 2006;Galea, Tracy, Norris, & Coffey, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…14,15 There is a small but growing literature on the impact of disasters on older [16][17][18][19][20][21] and oldest-old adults. 22,23 From an epidemiological perspective, older adults are less likely than younger adults to survive disaster.…”
mentioning
confidence: 99%